Pendaratan Micro-Drone berdasarkan Quick Response Code menggunakan DJI Tello dan Raspberry Pi - Satyaki Kusumayudha; Hurriyatul Fitriyah; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Unmanned Aerial Vehicle (UAV) or commonly called drone is an unmanned aircraft that is used for various needs. UAVs or Drones have a wide range of constructive applications such as remote inspection, agricultural monitoring, photography or filmmaking, Search and Rescue and package delivery. The Indonesian Flying Robot Contest (KRTI) is one of the national level robot contests held by the Directorate General of Higher Education (DIKTI) regularly every year. The Indonesian Flying Robot Contest has several divisions, one of which is Vertical Take Off Landing (VTOL). In 2021, the Vertical Takeoff landing competition division carries the theme of Delivery of Goods to the multi-storey apartment model using a VTOL vehicle based on QR code address recognition (Quick Response) and precision COLOR markings to support life in the post-pandemic New Order Era). By using the DJI Tello as a vehicle to be flown and the raspberry pi as a tool to program and using the pyzbar library to translate QR codes, we can find the computational time needed by DJI Tello to translate QR codes and also its accuracy in reading QR codes, as well as researchers. would like to find the percentage of DJI Tello's success in carrying out the mission to be given. The results of the DJI Tello accuracy test for reading the QR code are 86.67% and the time it takes for DJI Tello to read the QR code is 0.5959533 seconds. is 0.5959533 seconds.